2018
DOI: 10.7903/cmr.17673
|View full text |Cite
|
Sign up to set email alerts
|

Customer Engagement Behaviour in Social Media Advertising: Antecedents and Consequences

Abstract: With the rapid growth and development of social network services, companies have largely increased their advertising budgets for social media advertising. Social media advertising has attracted a great deal of attention among marketers and researchers. However, very few works of research have focused on social media advertising and have only concentrated on measuring clicking effects. This study established a model to analyze customers' engagement in social media advertising, the relationship among the anteced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
2
5
0
2
Order By: Relevance
“…Results also show that sociability does not impact satisfaction when using TikTok. Chiang et al [136] indicated that sociability does not influence satisfaction and this confirmed the dependability of the results to the present research. Nguyen et al [140] quote Norbert Elias, "the issue of human relationships constitutes the base of society".…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Results also show that sociability does not impact satisfaction when using TikTok. Chiang et al [136] indicated that sociability does not influence satisfaction and this confirmed the dependability of the results to the present research. Nguyen et al [140] quote Norbert Elias, "the issue of human relationships constitutes the base of society".…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies proposed that past time is positively affecting consumer satisfaction with TikTok. Quan-Haase et al [12,136] showed that past time is positively correlated to satisfaction using Facebook. Previous research has shown that providing entertainment through social media elicits positive emotions that affect people's attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Internet advertising has become increasingly popular in recent years, and advertisers are widely using online advertising tools to provide information about their company and products [38,39]. These tools also enable enterprises to create advertisement awareness, brand awareness, and purchase intention in consumers [40][41][42].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The research on customer engagement has experienced a frenzied growth in recent years (Harmeling et al, 2017). Some studies have tried to investigate the relationship between customer engagement and social media (Barger et al, 2016;Hinson et al, 2019) and SMA (Chiang et al, 2017;Schivinski et al, 2016). However, academic research on customer engagement related to social media is still limited.…”
Section: Introductionmentioning
confidence: 99%